A new minute species of Pristimantis (Amphibia: Anura: Craugastoridae) with a large head from the Yanachaga-Chemillén National Park in central Peru, with comments on the phylogenetic diversity of Pristimantis occurring in the Cordillera Yanachaga - Lehr, Edgar; Moravec, Jiří; Cusi, Juan Carlos; Gvoždík, Václav (European Journal of Taxonomy, 2017)
We describe a new minute species of the genus Pristimantis, P. boucephalus sp. nov., from the Yanachaga-Chemillén National Park, Región Pasco, Peru. The description is based on a freshly collected male specimen found at 2950 m a.s.l. in a cloud forest and four previously unidentified museum specimens consisting of two adult males, one subadult female and a juvenile from the Yanachaga-Chemillén National Park. The new species is mainly characterized by a snout–vent length of 13.4–14.5 mm in adult males (n = 3), and 12.5 mm in the only known subadult female, and is compared morphologically and genetically with other taxonomically and biogeographically relevant species of Pristimantis. The new species is characterized by its small size, disproportionally large head with short snout, absence of a tympanic annulus and membrane, and reddish-copper iris. Phylogenetically it belongs to a speciose clade, an as yet unnamed species group, comprising both montane (Andes, Guiana Shield) and lowland (Amazon) taxa from the northern part of South America. The new species is genetically close to the sympatric P. cruciocularis. Species of Pristimantis occurring in the Cordillera Yanachaga region in the Andes of central Peru are members of six divergent phylogenetic lineages.